Concept of Cyberspace and Types of Cyber Crimes in India: The Intersection of Technology and Crime (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Social networking sites have been very popular right from the beginning of the new millennium. These sites provided space for many to relax, connect with old friends and also get new also. But the cyber-criminal organizations have sadly misused these sites to serve their criminal acts. In the past couple of years, people started spending more time on these networks as the populations are gradually dependent on them. In the digital era, information technology growth influences the lives of people all over the world. Day after day, modern inventions and discoveries have broadened the science spectrum and created new problems for the legal community.